Eating in the middle : a mostly wholesome cookbook - Mitchell, Andie (Clarkson Potter/Publishers, 2016)
From the author of the New York times bestselling It was me all along, a cookbook for eating in balance, featuring mostly healthy recipes to help anyone stay fit, and a few "special occasion" sweets and entrees, with the author's moving story of weight loss and thoughts on managing cravings throughout. --